2023
DOI: 10.3389/fpsyg.2023.1126031
|View full text |Cite
|
Sign up to set email alerts
|

Climate anxiety, coping strategies and planning for the future in environmental degree students in the UK

Abstract: IntroductionThere is increasing recognition of the mental health burden of climate change and the effects on general well-being, even in those who have not (yet) experienced direct impacts. Climate anxiety, which is prominent among young people in particular, describes a state of heightened distress about the (future) effects of climate change. Despite evidence of a link between engagement in climate change issues and heightened climate anxiety, there is a dearth of knowledge on how this affects emerging profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Notably, the study revealed a correlation between the use of problem-focused coping strategies and higher rates of climate anxiety. This implies that despite the limited direct exposure to climate change impacts compared to more vulnerable regions, university students in the UK are actively involved in the issue, showcasing a commitment to addressing climate concerns through their academic pursuits and career aspirations [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the study revealed a correlation between the use of problem-focused coping strategies and higher rates of climate anxiety. This implies that despite the limited direct exposure to climate change impacts compared to more vulnerable regions, university students in the UK are actively involved in the issue, showcasing a commitment to addressing climate concerns through their academic pursuits and career aspirations [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the physical consequences of climate change are well-established, there is growing recognition of its psychological impacts. Environmental changes can impact psychological well-being, leading to stress and anxiety [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research supports the relationship between coping styles and self-efficacy. Daeninck et al (2023) found that positive coping styles among UK university students lead to greater self-control, while negative coping styles result in lower self-control. Similarly, Shi and Zhao (2014) demonstrated in a cross-sectional study with Chinese university students that positive coping styles, such as problem-solving and confidence in one's abilities, have a positive impact on overall selfefficacy, whereas negative coping styles, such as self-blame and self-doubt, negatively affect overall self-efficacy.…”
Section: The Reciprocal Association Between Self-efficacy and Coping ...mentioning
confidence: 97%